2011
DOI: 10.1002/art.30215
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin‐6 in a patient with tumor necrosis factor receptor–associated periodic syndrome: Assessment of outcomes following treatment with the anti–interleukin‐6 receptor monoclonal antibody tocilizumab

Abstract: In this report, we describe treatment outcomes in the first case of a patient with tumor necrosis factor receptor-associated periodic syndrome (TRAPS) treated with the anti-interleukin-6 (anti-IL-6) receptor monoclonal antibody tocilizumab. Since IL-6 levels are elevated in TRAPS, we hypothesized that tocilizumab might be effective. The patient, a 52-year-old man with lifelong TRAPS in whom treatment with etanercept and anakinra had failed, was administered tocilizumab for 6 months, and the therapeutic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…Cryopyrin-associated periodic syndrome and Schnitzler's syndrome, but not isolated chronic urticaria, respond poorly (or not at all) to glucocorticoids except at high doses of the order of a mg per kg (45). In HIDS, TRAPS, AOSD and soJIA however, oral glucocorticoids can be quite effective (7,34,40,46). Suspicion of autoinflammatory disease should prompt appropriate diagnostic measures to rule out or confirm CAPS, SchS or another autoinflammatory condition.…”
Section: How To Distinguish Isolated Chronic Urticaria From Autoinflamentioning
confidence: 99%
“…Cryopyrin-associated periodic syndrome and Schnitzler's syndrome, but not isolated chronic urticaria, respond poorly (or not at all) to glucocorticoids except at high doses of the order of a mg per kg (45). In HIDS, TRAPS, AOSD and soJIA however, oral glucocorticoids can be quite effective (7,34,40,46). Suspicion of autoinflammatory disease should prompt appropriate diagnostic measures to rule out or confirm CAPS, SchS or another autoinflammatory condition.…”
Section: How To Distinguish Isolated Chronic Urticaria From Autoinflamentioning
confidence: 99%
“…TRAPS treatment is aimed at preventing acute disease attacks, improving quality of life, and preventing the development of systemic reactive amyloidosis, the most troublesome long-term TRAPS complication [4][5][6]. Notably, despite considerable success achieved in recent times, TRAPS treatment is more challenging than other monogenic autoinflammatory diseases probably due to the genetic heterogeneity and protean clinical phenotype [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vaitla et al (10) reported tocilizumab outcomes in a patient with TRAPS. In their case, the evolving acute attack was aborted, and further attacks of TRAPS were prevented.…”
Section: Discussionmentioning
confidence: 99%